Quality and intake of mulberry (Morus alba), ramie (Bohemeria nivea (L) Gaud) and black sorghum (Sorghum almum) fodder in goats. - Elizondo-Salazar, Jorge Alberto (2004)
The experiment was carriedout in the Experimental Station Alfredo Volio Mata of theUniversity of Costa Rica. Mulberry, ramie and black sorghumfodder intake was evaluated and compared in nine La-Mancha goats with an average body weight of 38 (±1) kg,distributed in a Latin square design 3 x 3 repeated. The experimentaltreatments were: a) mulberry fodder, b) ramie fodderand c) black sorghum fodder. Mulberry had 90 days, ramie56 and black sorghum 70 days of re-growth. The foragewas given as chopped materials (stems and leaves). Samplesof offered and rejected material were gathered to analyze drymatter, crude protein and neutral detergent fiber content.Highly significant differences were observed (P≤0,01) forfresh forage, dry matter, crude protein and neutral detergentfiber intake by goats. Dry matter intake for the differenttreatments was within the range reported in the literature andthey were 1,94, 0,97 and 0,90% of body weight for the differentdiets respectively. Crude protein intake with mulberryand ramie was high enough to cover maintenance requirementsand they gave a surplus to obtain weight gains above50 grams per day. Fresh forage, dry matter, crude protein andneutral detergent fiber intake were higher for mulberry followedby the ramie diet.